Comparing Islamic and Non-Islamic College Students’ Personalities As Perceived by the Adversity Quotient - Feny Martina; Zelvia Liska Afriani; Syafryadin Syafryadin (AL-ISHLAH: Jurnal Pendidikan, 2023)
Adversity Quotient (AQ) influences an individual student’s personality in overcoming school challenges to perform well. This study aims to compare the AQ level of EFL students of Islamic (PTKI) and non-Islamic colleges (PTU) and its relationship with their achievement in language learning. This study is a mixed-method study with a sequential explanatory design. The population of this study was the last semester students of the English language education study program at PTKI and PTU in the city of Bengkulu, consisting of 357 students. The sample was selected randomly, consisting of 86 students from PTKI and the other 86 from PTU, with a total number of 172. The data were derived from the questionnaires of which conceptual guidelines from Stoltz. Descriptive statistics through the independent sample test was used to determine the difference in the average AQ results between PTKI and PTU. The results revealed 52,9% of students were in transition climbers. The second category, campers, consisted of 25% of students. The climbers' category was up to 20,35% students, and the last was transition campers revealed up to 0,02% of students. Neither PTKI nor PTU had any quitters. Moreover, the average AQ value of PTKI students is 153.78, while the average AQ value of PTU students is 142.23. The Sig. Levene's Test for Equality of Variances is 0.192, and its independent sample t-test is 0.000. These statistical data imply a significant difference between the average AQ results of students at PTKI and students at PTU.